2020
DOI: 10.4269/ajtmh.19-0690
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Childhood Zoonotic Enteric Infections in a Semirural Community of Quito, Ecuador

Abstract: Domestic animals in the household environment have the potential to affect a child's carriage of zoonotic enteric pathogens and risk of diarrhea. This study examines the risk factors associated with pediatric diarrhea and carriage of zoonotic enteric pathogens among children living in communities where smallholder livestock production is prevalent. We conducted an observational study of children younger than 5 years that included the analysis of child (n = 306) and animal (n = 480) fecal samples for Campylobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 74 publications
0
11
2
Order By: Relevance
“…Six studies suggested cohabitation with livestock was a risk factor of household contamination with livestock feces, intestinal parasite infection (containing Giardia lamblia ), both symptomatic and asymptomatic infection with Cryptosporidium spp., Campylobacter spp., and other zoonotic enteric pathogens (e.g., STEC, G. lamblia, Yersinia spp.) in CU5 ( 200 , 205 , 209 , 212 , 213 , 220 ). Other than exposure to livestock and their feces, a 2015 study associated frequent rodent sightings with the presence of non-typhoidal Salmonella in livestock, and Cryptosporidium infection in humans was positively correlated with presence of pet feces and scavengers in/around the households ( 221 , 224 , 225 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies suggested cohabitation with livestock was a risk factor of household contamination with livestock feces, intestinal parasite infection (containing Giardia lamblia ), both symptomatic and asymptomatic infection with Cryptosporidium spp., Campylobacter spp., and other zoonotic enteric pathogens (e.g., STEC, G. lamblia, Yersinia spp.) in CU5 ( 200 , 205 , 209 , 212 , 213 , 220 ). Other than exposure to livestock and their feces, a 2015 study associated frequent rodent sightings with the presence of non-typhoidal Salmonella in livestock, and Cryptosporidium infection in humans was positively correlated with presence of pet feces and scavengers in/around the households ( 221 , 224 , 225 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies defined the pathogens at the genus level (e.g., Salmonella, Cryptosporidium spp.) (202)(203)(204)(205), and 8 studies characterized pathogens with general biological groups only [i.e., enteric protozoa infection (206,207), intestinal parasite infection (208)(209)(210)(211)(212), enteric pathogen infection (213)]. We therefore defined pathogens as zoonotic (Z) and as zoonotic and/or anthroponotic (A/Z) as in section Enteric pathogens as determinants of EED or undernutrition in children under five.…”
Section: Risks Factors Of Exposure To or Infection With Zoonotic Enteric Pathogens Associated With Smallholder Livestock Productionmentioning
confidence: 99%
“…Zoonotic enteric parasites are ubiquitous and remain a public health threat to humans due to their close contact with domestic and wild animals 34 . Intestinal parasites such as Cryptosporidium spp., Blastocystis , and Giardia have animal hosts that facilitate their human transmission; in this sense, several studies have shown an important role of domestic animals as reservoirs in the transmission of numerous enteroparasites 9 , 35 , 36 . In our study, all the patients evaluated were adults (over 18 years old) and, on average, the parasitized individuals were older than those non-parasitized, which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that cattle and other ruminants are the primary hosts of Shiga toxin-producing E. coli (STEC), 4,27 which can be transmitted to humans via exposure to ruminant feces, direct contact with ruminants, and consumption of contaminated meat, milk, and water. 28 Atypical enteropathogenic Escherichia coli (aEPEC) is present in the feces of many domestic animals including cattle, sheep, pigs, and chickens, 4,29,30 with evidence of transmission to children, 29 though the pathogenicity of animal aEPEC strains remains unclear. 4,27 Both non-typhoidal Salmonella and Campylobacter have many animal reservoirs (primarily poultry and cattle) and are transmitted through foodborne routes, mainly via consumption of contaminated poultry meat and dairy products.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence has linked household livestock ownership in LMICs to enteropathogen infections in young children, including in Ecuador, 29,30 Peru, 33 Egypt, 34 Ethiopia, 14 and Lao People's Democratic Republic. 35 Four of these studies found that exposure to household chickens and their feces was associated with Campylobacter jejuni infection in children, 14,29,33,34 suggesting that in low-resource settings, direct fecal exposure is an important transmission pathway for Campylobacter infection.…”
Section: Introductionmentioning
confidence: 99%